Small heterodimer partner-interacting leucine zipper protein suppresses pain and cartilage destruction in an osteoarthritis model by modulating the AMPK/STAT3 signaling pathway - Jeonghyeon Moon; Keun-Hyung Cho; JooYeon Jhun; JeongWon Choi; Hyun-Sik Na; Jeong Su Lee; Seung Yoon Lee; Jun-Ki Min; Anan Shetty; Sung-Hwan Park; Seok Jung Kim; Mi-La Cho (Arthritis Research & Therapy)
Abstract Objective Osteoarthritis (OA) is a degenerative joint disease caused by the breakdown of joint cartilage and adjacent bone. Joint injury, being overweight, differences in leg length, high levels of joint stress, abnormal joint or limb development, and inherited factors have been implicated in the etiology of OA. In addition to physical damage to the joint, a role for inflammatory processes has been identified as well. Small heterodimer partner-interacting leucine zipper protein (SMILE) regulates transcription and many cellular functions. Among the proteins activated by SMILE is the peroxisome proliferator-activated receptor (PPAR) γ, which mediates the activities of CD4 + T helper cells, including Th1, Th2, and Th17, as well as Treg cells. PPAR-γ binds to STAT3 to inhibit its transcription, thereby suppressing the expression of the NF-κB pathway, and in turn, the expression of the inflammatory cytokines interferon (IFN), interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α, which are sub-signals of STAT3 and NF-κB. Methods OA was induced in control C57BL/6 mice and in C57BL/6-derived SMILE-overexpressing transgenic (SMILE Tg) mice. The protein expression levels in the joint and spleen tissues were analyzed by immunohistochemistry and immunofluorescence images. In addition, flow cytometry was performed for detecting changes of the changes of immune cells. Results Less cartilage damage and significantly reduced levels of OA biomarkers (MMP13, TIMP3 and MCP-1) were observed in SMILE Tg mice. Immunohistochemistry performed to identify the signaling pathway involved in the link between SMILE expression and OA revealed decreased levels of IL-1β, IL-6, TNF-α, and phosphorylated AMPK in synovial tissues as well as a significant decrease in phosphorylated STAT3 in both cartilage and synovium. Changes in systemic immune cells were investigated via flow cytometry to analyze splenocytes isolated from control and SMILE Tg mice. SMILE Tg mice had elevated proportions of CD4 + IL-4 + cells (Th2) and CD4 + CD25 + Foxp3 + cells (Treg) and a notable decrease in CD4 + IL-17 + cells (Th17). Conclusion Our results show that overexpressed SMILE attenuates the symptoms of OA, by increasing AMPK signaling and decreasing STAT3, thus reducing the levels of inflammatory immune cells.